2018
DOI: 10.1002/ajpa.23478
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal activity in wild chimpanzees (Pan troglodytes): Evidence for flexible sleeping patterns and insights into human evolution

Abstract: Chimpanzee terrestrial nocturnal activity appears widespread yet infrequent, which suggests a consolidated sleeping pattern. Nocturnal activity may be driven by the stress of high daily temperatures and may be enabled at low levels of human activity. Human activity may exert a relatively greater influence on chimpanzee nocturnal behavior than predator presence. We suggest that chimpanzee nocturnal activity is flexible, enabling them to respond to changing environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 93 publications
(159 reference statements)
2
48
1
Order By: Relevance
“…While it can be argued that this violates statistical rules of independence (as can any behavioral sequence involving individuals or groups within a population), we believe that this is used appropriately here because each night was separated by 12 hr of daylight and within that time, each of our four baboon groups had access to multiple sleeping sites, and could move in any of many potential directions relative to where they slept the night before, that is, where they slept each night was likely determined at least as much or more by where they moved in the preceding 12 hr than where they slept the night before (e.g., Markham et al, ; Pebsworth, Macintosh, Morgan, & Huffman, ; Shreier and Grove, ). Nights or group‐nights are also common units of analysis in other studies of nocturnal behavior in diurnal primates (e.g., Markham et al, ; Pruetz, ; Tagg et al, ). We used sleeping site visits as the unit of analysis for leopards.…”
Section: Methodsmentioning
confidence: 99%
“…While it can be argued that this violates statistical rules of independence (as can any behavioral sequence involving individuals or groups within a population), we believe that this is used appropriately here because each night was separated by 12 hr of daylight and within that time, each of our four baboon groups had access to multiple sleeping sites, and could move in any of many potential directions relative to where they slept the night before, that is, where they slept each night was likely determined at least as much or more by where they moved in the preceding 12 hr than where they slept the night before (e.g., Markham et al, ; Pebsworth, Macintosh, Morgan, & Huffman, ; Shreier and Grove, ). Nights or group‐nights are also common units of analysis in other studies of nocturnal behavior in diurnal primates (e.g., Markham et al, ; Pruetz, ; Tagg et al, ). We used sleeping site visits as the unit of analysis for leopards.…”
Section: Methodsmentioning
confidence: 99%
“…Camera-trap events were defined as consecutive video clips from the same camera that were triggered within 15 min of each other, where individuals within an event can be counted and identified, similar to previous studies [42,43]. This interval has been validated to best reflect true party size estimates in chimpanzees therefore providing a reliable estimate of grouping patterns of wild apes [44].…”
Section: Coding Of Camera-trap Videosmentioning
confidence: 99%
“…Meanwhile, Tagg et al. () used trap‐camera footage to examine terrestrial nocturnal activity in wild chimpanzees—behavior that had not been systematically documented previously, owing to the logistical difficulties. Combining camera footage with ecological survey data, they concluded that nighttime terrestrial activity was widespread and flexible—occurring at all hours of the night—but infrequent, consistent with consolidated sleeping patterns.…”
Section: Integrative Methods and New Analytical Approachesmentioning
confidence: 99%